Effect of Financial Leverage on the Financial Performance of Jordanian Public Shareholding Companies: Applied Study on the Financial Sector of Jordan for the Period of 2015-2019 - Aloshaibat, Sulieman Daood (International Journal of Economics and Financial Issues, 2021)
This paper aimed to demonstrate the effect of financial leverage measured through the liability-to-equity ratio on financial performance measured by the return on equity and the return on assets (ROA) in Jordanian public shareholding financial companies listed on the Amman stock Market. To achieve the objectives of the study, the descriptive analytical approach and simple regression analysis were used. The study population was represented by public shareholding companies listed on the Amman Financial Market during the period of 2015–2019. A total of 25 companies were selected as for the study sample. The study concluded that financial leverage affects the financial performance measured through the return on property rights in Jordanian public shareholding companies(ROE) and financial leverage does not affect financial performance measured through ROA. The study recommended that financial departments in financial institutions should identify factors that influence ROA that serve the company and work to achieve the optimal exploitation. For assets that generate additional profits to maximise the wealth of owners. Keywords: Financial leverage, Financial performance, Return on equity, Return on assets JEL Classification: G DOI: https://doi.org/10.32479/ijefi.11246